The Significance of Professional, Personal and Business Networks to Academic Entrepreneurs - Abd Rahim, Noorlizawati; Mohamed, Zainai; Amrin, Astuty; Masrom, Maslin (Journal of Research Management and Governance, 2019)
The degree of informational support academic scientists acquired from social network is associated with greater perceived feasibility that may influence their involvement in the research commercialization. Social capital has been commonly assessed by measuring the number of direct contacts from business and industry networks as well as the frequency of establishing new contacts. These approaches, however, have not adequately explained how social capital is beneficial to their entrepreneurial endeavor. This paper attempts to validate social capital as a formative construct using partial least squares structural equation modeling (PLS-SEM) to explore the relative importance of personal, professional and business networks to academic entrepreneurs in their technology transfer pursuit. A sample of 115 academic entrepreneurs of a Malaysia public research university was surveyed. The analyses of formative measurement model to evaluate construct validity, collinearity and significance of indicators revealed that scientists’ personal network is the most important social resource that facilitate and encourage them in the technology transfer pursuit, followed with business partners and potential investors. Although scientists have a large professional network through their attendance to conference, workshops and seminars, however, these platforms are often themed to focus more on sharing scientific knowledge rather than on academic entrepreneurship.